2019
DOI: 10.1111/aos.14248
|View full text |Cite
|
Sign up to set email alerts
|

Implication of inflammatory cytokines in the aqueous humour for management of macular diseases

Abstract: Purpose: To characterize profile of cytokines in aqueous humour of common macular diseases during intravitreal anti-VEGF therapy. Methods: Aqueous humour from eyes with central retinal vein occlusion (CRVO), branch retinal vein occlusion (BRVO), diabetic macular oedema (DME), neovascular age-related macular degeneration (nAMD) or pathologic myopia associated choroidal neovascularization (pmCNV) was sampled prior to 1st (n = 144) and 2nd (n = 48) intravitreal anti-VEGF therapy. Cytokines including vascular endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…In the retina, we found that 4 molecules were upregulated in systemic hypoxia: VEGF, IL-1β, IL-22, and MCP3. Retinal immune profiling for systemic hypoxia has not previously been reported prior to our study, but upregulation of immune molecules such as VEGF and IL-1 has been wellreported in retinal vascular diseases associated with hypoxia, such as proliferative diabetic retinopathy [59,60], macular edema associated with branch retinal vein occlusion [61] and central retina vein occlusion [62][63][64]. IL-6, TNF-α and IL-1β upregulation and evidence of CNS inflammation have been well-reported in animal models of systemic hypoxia [65][66][67].…”
Section: Discussionmentioning
confidence: 59%
“…In the retina, we found that 4 molecules were upregulated in systemic hypoxia: VEGF, IL-1β, IL-22, and MCP3. Retinal immune profiling for systemic hypoxia has not previously been reported prior to our study, but upregulation of immune molecules such as VEGF and IL-1 has been wellreported in retinal vascular diseases associated with hypoxia, such as proliferative diabetic retinopathy [59,60], macular edema associated with branch retinal vein occlusion [61] and central retina vein occlusion [62][63][64]. IL-6, TNF-α and IL-1β upregulation and evidence of CNS inflammation have been well-reported in animal models of systemic hypoxia [65][66][67].…”
Section: Discussionmentioning
confidence: 59%
“…In addition, models of glaucoma have shown the presence of macrophages and T-lymphocytes in the eye along with autoantibodies to proteins of the retina [3,4,29,30]. Models of RP have also shown similar features, including monocytic phagocytosis of both diseased and healthy retinal cells as well as numerous cytokines such as interleukin-1, interleuken-6, vascular endothelial growth factor, and others [4,31,32]. While the molecular mechanisms of the primary genetic assault have been teased out by copious amounts of work using cell culture and animal models for many RDs (i.e., loss of outer segment formation, disrupted visual cycle, etc.)…”
Section: Discussionmentioning
confidence: 98%
“…Although the pathogenic causes of RVO are unknown, it is hypothesized that inflammatory indicators play an important role in the disease’s onset. Several inflammatory factors, including IL6, IL8, ICAM-1, MCP-1, IL1-, IL 17-E, and TNF-α, were found to be higher in the aqueous or vitreous of RVO eyes [ 6 – 8 ], prompting the FDA to approve an anti-inflammatory drug (Ozurdex, an intravitreal dexamethasone implant) for treating macular edema following RVO in 2009. As a result, several prospective trials have shown the efficacy and safety of an intravitreal dexamethasone implant for the treatment of RVO-related macular edema [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%